2007
DOI: 10.1111/j.1540-8175.2007.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Cardiomyopathy Is Associated with More Severe Left Ventricular Dyssynchrony than Is Hypertensive Left Ventricular Hypertrophy

Abstract: The presence of LVH is thus not always associated with LV dyssynchrony. However, the greater reduction of regional strain and severe LV dyssynchrony in HCM may contribute to the adverse cardiovascular outcomes associated with this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…This hypothesis is further supported by previous studies demonstrating a positive correlation between LA size and LV wall thickness [3,4,22] and a higher degree of cell damage and fibrotic change in the thicker ventricular wall [23]. Moreover, it was recently reported in a study of 2-dimensional speckle tracking that patients with HCM had more severe LV dyssynchrony than those with hypertensive heart disease [24]. Since the ventricular systolic phase coincides with LA relaxation, there may be transmission of the LV myocardial contraction pattern to the thinwalled LA, with a resultant increase in the degree of reservoir dyssynchrony.…”
Section: Present Observationssupporting
confidence: 75%
“…This hypothesis is further supported by previous studies demonstrating a positive correlation between LA size and LV wall thickness [3,4,22] and a higher degree of cell damage and fibrotic change in the thicker ventricular wall [23]. Moreover, it was recently reported in a study of 2-dimensional speckle tracking that patients with HCM had more severe LV dyssynchrony than those with hypertensive heart disease [24]. Since the ventricular systolic phase coincides with LA relaxation, there may be transmission of the LV myocardial contraction pattern to the thinwalled LA, with a resultant increase in the degree of reservoir dyssynchrony.…”
Section: Present Observationssupporting
confidence: 75%
“…It was characterized by the prolongation of LV IRT, smaller Ea, and greater E/Ea compared to control subjects. Previous studies have demonstrated that the presence of severe LV dyssynchrony [2,5] and regional systolic and relaxation abnormalities were related to impaired global LV relaxation in HCM [3,4,6,18,19]. Moreover, another study showed that heterogeneous contraction of the hypertrophied region accounted for global relaxation impairment in HCM.…”
Section: Discussionmentioning
confidence: 93%
“…Heterogeneity of regional left ventricular (LV) function has been reported in hypertrophic cardiomyopathy (HCM) and this is considered to play an important role in the relaxation abnormality [1][2][3][4][5][6]. Recently, the presence of apex-to-base disparity in the regional timing of early diastolic LV lengthening, based on the electromechanical activation sequence of LV, has been recognized as an important determinant of LV systolic and diastolic properties in animal models [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…1 There has been increased recognition that LV dyssynchrony also exists in patients without HF but with other cardiac diseases, including hypertension, 2 coronary artery disease (CAD) 3 and cardiomyopathy. 4,5 Dyssynchrony has been measured using a variety of echocardiographic parameters based on different imaging techniques, 6 including pulsed-wave tissue Doppler imaging (TDI), colorcoded TDI, tissue tracking, displacement mapping, strain and strain rate imaging, and tissue synchronization imaging. TDI is the most extensively tested method.…”
Section: Introductionmentioning
confidence: 99%